Mathematical Model of "Working Gap – Pad – Elastic Support" System for Rotor Support Tilting-pad Journal Bearing. (2017) - Parovay, E.F.; Falaleev, S.V.
Abstract: The object of this work is a starved tilting-pad journal bearing (TPJB) with an elastic support of pads. Bearing design includes four pads and an elastic support made of a porous elastic-damping material "metal analogue of rubber" (MR). The elastic support allows pads to tilt and self-adjust. Thus elastic-damping properties of the pad support are adjusted automatically and prevent development of "pad flutter". This bearing is a perspective solution for gas turbine engines (GTE) issues connected with the application of rolling bearings. Furthermore, in comparison with traditional bearings, TPJB with an elastic support of pads are dynamically stable and has high performance capabilities. Design of TPJB and MR parts is a complex process that requires experimental investigations. In addition, a design technique has not been developed yet. The objective of this work is to develop a mathematical model of "working gap - pad - elastic support" system as part of the required design technique. Developed mathematical model allows to determine optimum values of the MR parameters on the basis of the oil flow characteristics (CFD results). The developed TPJB design technique is innovative, it takes into account the design features and their working process. TPJB with MR elastic support of pads is an effective solution for heavy-loaded rotors that require high dynamic stability and long life of the bearings.